Physics of croquet. (25th October 2016) - Cross, Rod
Abstract: Croquet is a sport that is similar to billiards in that it involves the collision of one ball with another. Measurements and calculations are presented for three typical shots, one known as a straight croquet, one known as a split croquet and the other known as a push or roll shot. Each exhibit collision phenomena that could serve to illustrate aspects of an introductory course in mechanics, and that could also provide challenges even for more advanced students.